(untitled) (Research, Society and Development, 2022)
This study aimed to compare the commercial product Valio® based on orange oil with mineral oil and adjuvant in the deposition of spray droplets of chemical products on the desired targets in land application. The test was carried out under field conditions, using the common bean crop in the municipality of Rio Verde, Goiás, at the experimental station MRE Agropesquisa Ltda, located at geographic coordinates (17°55’23.68"S and 51°8’45.32 "THE). For the deposition of drops, three water-sensitive paper collectors were placed transversally to the application line along the spray bar. The design was completely randomized with four replications, considering the control as 0 mL ha-1 of commercial product in the syrup. The water-sensitive papers were scanned and analyzed using the DepositScan® pesticide deposition analysis software and then tabulated in Excel®. Drop size, drop number, coverage and volume were defined for all treatments in different collection positions. The commercial product Valio® (orange oil) had a satisfactory performance in terms of application quality.